Meningkatkan hasil belajar murid melalui model (TGT) teams Games Tournament dalam pembelajaran PKn kelas IV SD Negeri 26 Tamanroja Kecamatan Labakkang Kabupaten Pangkep - Rismawati Rismawati; Mardiana Mardiana (JED (Jurnal Etika Demokrasi), 2018)
This study can improve the learning outcomes of Civics through the learning model TGT (Team Tournament Match) in the fourth class in SD 26 Tamanroja Sub-district Labakkang Pangkep regency. This type of research is a classroom action research (classroom action class) consisting of 2 cycles where each cycle is held 4 times a meeting. Implementation procedures, observation and reflection. Subjects in this study were fourth grade students of SD Negeri 26 as many as 44 people. The collected data were analyzed using quantitative and qualitative analysis. The result of quantitative analysis shows that there is an increase of learning result which can be seen from average score in cycle I due to student learning result equal to 69,13 with ideal score 100 which is in low category, whereas in cycle II become 79,09 with ideal score 100 that is in the medium category. Qualitatively expected to increase in language, active, and student motivation to learn Civics. Based on the results of this study can be concluded in the learning PKN through learning model teams tournament games (TGT) can improve the learning outcomes of fourth grade students of SD Negeri 26 Tamanroja District Labakkang Pangkep District.Keywords: Learning Outcomes, Tournament Match Team (TGT), Student